2013
DOI: 10.1016/j.jtcvs.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of quality and cost indicators by surgical specialty for lobectomy of the lung

Abstract: This review found that currently measurable indicators for quality of care were significantly superior and overall charges were significantly reduced when a lobectomy for non-small cell lung cancer was performed by a cardiothoracic surgeon rather than by a general surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Although the current study could not take into account surgeon practice patterns or specialty because of constraints of the NCDB, it is known that general surgeons perform most of the lung cancer re-sections in the United States [5] A single health system review of more than 6,000 patients receiving a lobectomy for NSCLC (stages I to IIIB) revealed that even though patients under the care of a general thoracic surgeon were older, had higher Charlson comorbidity scores, and were more likely to have stage IIIA tumors, a significant decrease in hospital length of stay, overall admission charges, and perioperative morbidity and mortality was found [6]. Furthermore, the rate of adherence to National Comprehensive Cancer Network guidelines was also significantly higher [6]. A review with more than 25,000 patients receiving pulmonary resection in the national Medicare database also demonstrated a lower perioperative mortality rate for fellowship-trained thoracic surgeons compared with general surgeons and found that this difference between surgeon specialty persisted at high-volume hospitals [7].…”
Section: Discussionmentioning
confidence: 99%
“…Although the current study could not take into account surgeon practice patterns or specialty because of constraints of the NCDB, it is known that general surgeons perform most of the lung cancer re-sections in the United States [5] A single health system review of more than 6,000 patients receiving a lobectomy for NSCLC (stages I to IIIB) revealed that even though patients under the care of a general thoracic surgeon were older, had higher Charlson comorbidity scores, and were more likely to have stage IIIA tumors, a significant decrease in hospital length of stay, overall admission charges, and perioperative morbidity and mortality was found [6]. Furthermore, the rate of adherence to National Comprehensive Cancer Network guidelines was also significantly higher [6]. A review with more than 25,000 patients receiving pulmonary resection in the national Medicare database also demonstrated a lower perioperative mortality rate for fellowship-trained thoracic surgeons compared with general surgeons and found that this difference between surgeon specialty persisted at high-volume hospitals [7].…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC patients have better survival if they are treated in high volume surgical centres, even if they are older, of low socioeconomic status or have comorbidities . In addition, those treated by thoracic surgeons have lower post‐operative mortality and morbidity and better adherence to established practice standards than patients treated by general surgeons …”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, those treated by thoracic surgeons have lower post-operative mortality and morbidity and better adherence to established practice standards than patients treated by general surgeons. 7,8 Most studies of the effects of distance to specialist care on treatment of NSCLC have been done in the UK. The majority of them have shown that patients' access to surgical treatment is influenced by distance, clinician specialty and hospital of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although economic analyses have shown HF clinics to be a cost-effective means of disease management, it is not known which specific structure and process measures are most important to reduce health care costs. [16][17][18] Previous investigators have focused on drivers of HF-related costs at the end of life 19,20 ; however, guidelines suggest that referrals to HF clinics should occur early after a HF hospitalization, a period that represents a distinct phase of HF-related costs. [16][17][18] Previous investigators have focused on drivers of HF-related costs at the end of life 19,20 ; however, guidelines suggest that referrals to HF clinics should occur early after a HF hospitalization, a period that represents a distinct phase of HF-related costs.…”
mentioning
confidence: 99%